Production of soybean in association with the arbuscular mycorrhizal fungi Rhizophagus clarus cultivated in field conditions - Oliveira, Thales Caetano de; Uehara, Hyuri Mendes; Silva, Luan Dionísio da; Tavares, Germanna Gouveia; Santana, Letícia Rezende; Cabral, Juliana Silva Rodrigues; Souchie, Edson Luiz; Mendes, Giselle Camargo (Revista de Ciências Agroveterinárias, 2019)
Soybeans are key to agribusiness progress, but their production can be affected by climate change. Thus, alternatives that increase the yield of the plants under adverse conditions are fundamental, and the arbuscular mycorrhizal fungi (FMA) stand out. Therefore, they associate the roots of the plants, increasing the absorption of water and nutrients. Thus, the objective of this work was to evaluate soybean yield in the field experiment in association with FMA Rhizophagus clarus under conditions of irrigated and non-irrigated system. In the end, agronomic and symbiosis parameters were evaluated with FMA. The experimental design was in randomized blocks with subdivided plots, the means obtained were submitted to analysis of variance and compared by the Tukey test (5%), using SISVAR software. Soybean plants when associated with FMA and cultivated in non-irrigated conditions, obtained higher productivity than plants in the irrigated system and weight of 1000 grains. In this way, it is concluded that inoculation benefits soybean yield under non-irrigated system conditions.